2020
DOI: 10.3390/ma13163485
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Ultrasonic Spray Pyrolysis Processing of Noble Metal Nanoparticles—Review

Abstract: In the field of synthesis and processing of noble metal nanoparticles, the study of the bottom-up method, called Ultrasonic Spray Pyrolysis (USP), is becoming increasingly important. This review analyses briefly the features of USP, to underline the physical, chemical and technological characteristics for producing nanoparticles and nanoparticle composites with Au and Ag. The main aim is to understand USP parameters, which are responsible for nanoparticle formation. There are two nanoparticle formation mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 103 publications
1
31
0
Order By: Relevance
“…We found that the wedge formed by the displacement of H 2 was technologically problematic, as H 2 escaping through the tube back into the evaporation zone can cause too rapid a reaction with the precursor compound at a lower temperature, leading to irregular nanostructures with inadequate chemical composition. Such nanoparticles are unusable for many intended applications, as they do not achieve the required properties related to their size and structure [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the wedge formed by the displacement of H 2 was technologically problematic, as H 2 escaping through the tube back into the evaporation zone can cause too rapid a reaction with the precursor compound at a lower temperature, leading to irregular nanostructures with inadequate chemical composition. Such nanoparticles are unusable for many intended applications, as they do not achieve the required properties related to their size and structure [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic spray pyrolysis (USP) is a method of nanoparticle synthesis. Compared to other methods (laser ablation [4], nanoemulsion [5], reduction in liquid [3]) it enables the continuous synthesis of nanoparticles and represents a promising method for their industrial production [6]. The existing USP device (Figure 1) [7], which has three temperature zones, allows for the controlled synthesis of metal nanoparticles on a laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…They elucidated in detail two USP mechanisms for forming NPs depending on the state of precursor: Droplet-To-Particle (DTP) and Gas-To-Particle (GTP). In contrast to other methods of NPs production, USP is considered a far more cost-effective approach and can be easily scaled up to the industrial level with acceptable productivity in droplet sizes [105] .…”
Section: Nanobiomaterials Synthesis Induced By Physical Effectsmentioning
confidence: 99%
“…AuNPs were produced with a USP device located in Zlatarna Celje d.o.o., Celje, Slovenia. The USP device uses a custom-made ultrasonic generator with a 1.6 MHz ultrasonic transducer LIQUIFOG II (Johnson Matthey Piezo Products GmbH, Redwitz, Germany) as its base [29][30][31]. The ultrasonic generator produces aerosol droplets from the Au precursor, which are transported by carrier gas (N2) into a heating furnace, which is composed of 3 zones.…”
Section: Preparation Of Aunpsmentioning
confidence: 99%